The The Realization of Interpersonal, Ideational, and Textual Meaning in Graduate Students’ Research Paper - Wardani, Hesti Eka; Sutopo, Djoko; Faridi, Abdurrahman (English Education Journal, 2019)
Systemic Functional Linguistics offers a model of approach in analyzing discourse concerning to reveal how language is used to negotiate meaning. Research paper, also known as research article presents students’ work in a process of academic which involving students’ understanding and interpreting knowledge in applying knowledge in a certain phenomenon. Therefore, this study aimed to explain the realization of Interpersonal, Ideational, and Textual Meaning in graduate students’ research paper. Descriptive qualitative research design was used in this study with ten research papers form graduate students of English language education program in Universitas Negeri Semarang were taken as the subject of analysis. Mood, Transitivity, and Theme analysis was used to achieve the data analysis. The findings revealed that the meanings were realized by the students’ language choice. Interpersonal meaning realized in the research papers showed that the research papers were carrying the speech role as giving information. Moreover, the students took role as the information giver in the third person point of view. Ideational meaning realized in research papers showed that the students presented their experience in state of being and doing through relational process and material process with help of other process types, participant roles and circumstances to support their presenting. Textual meanings were realized through the use of theme structure by giving high concern on the subject of the clause as the main delivered message point. The realization of the meanings also could give benefit to students in having the guideline when they are proposed to write research paper.